The Educational styles derived from Prophet Mousa’s Story peace in Surt taha: An analytical study - Aslan, Omar Mohammed Ali (Journal of Educational and Psychological Sciences, 2020)
This study aims at deducing the educational styles learned from Prophet Moses story peace be upon him found in Surt taha (Verses 9- 99), and the Department of current research into four topics, The first topic dealt of the teaching styles, The second section the dealt with Psychological educational styles, and while devoted the third section the Classroom management styles, and the fourth topic dealt the Linguistic styles. The researcher used the descriptive analytic method to derive The Educational styles from the verses included under that dimension, the verses in Sort taha (9- 99) are under consideration in this research.The research revealed the presence of fourteen teaching styles in Mousa’s Story peace in Surt taha, the most common of these teaching Styles the decision- making, repetition, and the teaching style depending on brain activity, demonstration, and The results showed that there three Psychological educational styles such as (Preparation, Intrusion and intimidation, Spread security, ), And six methods of classroom management for example punishment style, And two styles of language.The study concluded with some recommendations including Conducting educational research relevant to the verses and chapters of the Holy Quran, and spreading and Urging educators to take advantage of educational methods contained in the sora and work on applying, and emphasizing the importance of taking them in the field of education and in preparing teachers and training them during service.
Keywords: Educational styles; Mousa’s Story; Surt taha